Upgrading of Rwakiseta Road from Gravel to a Double Surface Bituminous Road. - Akanyijuka, Baram (Kabale University, 2023)
This report consists of a detailed proposed design for upgrading Rwakisenta road to a bituminous Paved surface which stretches a distance of 638M. The main objective was to a design flexible pavement with respect to the route, geometry, drainage and pavement. This was done by assessing the current traffic using the road, existing geometry, pavement structure and designing an appropriate drainage system. The project road was characterized by a broken back curve, reverse curve and sharp curves, which brought about so many traffic delays. Lab and field tests, surveys, consultations, and observations were some of the methods that were used to collect data . From the results obtained, the Average Daily Traffic was 200 Vehicles/day, Motorcycles taking up the greatest percentage of traffic (45%), the subgrade at section at different sections was averagely found unsuitable having a CBR of 28%, and most of the curves were substandard having a radius of less than 100m. A trapezoidal channel section, culverts were designed to cater for drainage. A double surface dressing layer of 50mm overlying a base of gravel thickness 175mm and also 175mm gravel thick sub base The ADT showed that the road was due for upgrading considering the Ministry of Works and transports' criterion for upgrading a road in an urban setting with more than 20000Vehicles/day. A realignment was proposed with curves having a minimum radius of 100m, continuous maintenance of the drains will be necessary so as to prevent silting. Quality control should be ensured for materials in accordance with the specifications as stipulated.